SWOT Analysis in Strategic Planning of Start Technology Company Up - Nawawi, Muhammad Rifa (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
SWOT analysis is a working strategic framework that helps startups understand their position in the market by identifying strengths, weaknesses, opportunities and threats. Using this information, startups can develop strategies that capitalize on internal strengths, address weaknesses, seize opportunities, and mitigate threats. This helps them strengthen their position, optimize growth and better deal with market changes. Thus, SWOT analysis is a valuable tool in developing a startup strategy to achieve long-term success.